Transformasi Digital dan Perlindungan Hak Asasi Manusia Rekrontruksi Kesadaran Hukum melalui Pendekatan HAM dan Islamic Sociological Jurisprudence Theory - Ahmad Muhamad Mustain Nasoha; Citra Nurhasanah; Faiza Chaya Syadifa; Anisa Nur Anjarwati (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Digital transformation has brought significant changes to human life, including in the realms of law and the protection of human rights. The rapid development of information technology has introduced new challenges in the form of human rights violations in the digital space, such as privacy breaches, the spread of misinformation, hate speech, and the increasing prevalence of cybercrime. This phenomenon indicates that the digital sphere not only offers benefits but also poses serious risks to the protection of individual rights. This study aims to analyze the reconstruction of legal awareness in addressing these challenges through a human rights approach and the Islamic Sociological Jurisprudence Theory. The research employs a normative legal method with conceptual and sociological approaches, emphasizing the analysis of literature and applicable legal norms. The findings reveal that conventional legal approaches have not been fully capable of addressing the complexity of evolving digital issues. Therefore, an integration of human rights principles and a contextual Islamic legal approach through Islamic Sociological Jurisprudence is required. This approach highlights the importance of maqāṣid al-sharī‘ah, substantive justice, and legal awareness that is adaptive to social change. Thus, the reconstruction of legal awareness becomes a key element in establishing effective, just, and sustainable human rights protection in the digital era.